2017
DOI: 10.1021/acsami.7b03449
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Flexible Aramid Nanofiber/Graphene Layer-by-Layer Electrodes

Abstract: Aramid nanofibers (ANFs), or nanoscale Kevlar fibers, are of interest for their high mechanical performance and functional nanostructure. The dispersible nature of ANFs opens up processing opportunities for creating mechanically robust and flexible nanocomposites, particularly for energy and power applications. The challenge is to manipulate ANFs into an electrode structure that balances mechanical and electrochemical performance to yield a robust and flexible electrode. Here, ANFs and graphene oxide (GO) shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 66 publications
3
75
0
Order By: Relevance
“…39 ANFs have been used in a variety of applications including energy storage. 22,[40][41][42][43][44][45][46][47][48][49][50][51] ANF/PEDOT:poly(styrene sulfonate) electrodes exhibited specific capacitance of 112 F/g, Young's modulus of 5 GPa, and tensile strength of 76 MPa. 48 Last year, branched aramid nanofibers (BANFs) were first reported and were shown to bear further improved mechanical properties over ANFs.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…39 ANFs have been used in a variety of applications including energy storage. 22,[40][41][42][43][44][45][46][47][48][49][50][51] ANF/PEDOT:poly(styrene sulfonate) electrodes exhibited specific capacitance of 112 F/g, Young's modulus of 5 GPa, and tensile strength of 76 MPa. 48 Last year, branched aramid nanofibers (BANFs) were first reported and were shown to bear further improved mechanical properties over ANFs.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…According to Figure a, similar results can also be found that peaks at δ (5.97)(a), δ (6.56)(b) and δ (7.26)(c) which belongs to H of imidazole compound all move to low field after adding PBA‐HCl and it moves more obviously with increasing amount of PBA‐HCl. Moreover, pK a of imidazole compound is nearly at 6.95 and it is larger than that of benzimidazole moiety whose pK a is nearly at 5.49 . Larger pK a brings about stronger proton affinity and makes imidazole compound more easier to complex with HCl.…”
Section: Methodsmentioning
confidence: 98%
“…Moreover, pK a of imidazole compound is nearly at 6.95 and it is larger than that of benzimidazole moiety whose pK a is nearly at 5.49. [7] Larger pK a brings about stronger proton affinity and makes imidazole compound more easier to complex with HCl. Therefore, formation of IDC is confirmed in presence of PBA-HCl and imidazole compound.…”
mentioning
confidence: 99%
“…Although ANF shows impressive insulation properties, its superior mechanical properties, high aspect ratio, good film‐forming property, and excellent thermal stability make it a perfect alternative to be integrated with conductive nanomaterials to construct flexible, robust, and conductive ANF‐based electronics that have promising applications in nanofluidic osmotic power generators, [ 102 ] composite electrodes, [ 103,104 ] and electromagnetic interference (EMI) shielding. [ 17 ] For example, current 2D nanofluidic architectures show low‐efficiency transport dynamics and undesirable power densities due to the insufficient charge densities of the components.…”
Section: Applications Of Anfmentioning
confidence: 99%
“…In addition, flexible graphene‐based supercapacitors have attracted increasing attention due to their outstanding electrical properties, but they suffer from inferior mechanical strength (tensile strength <15 MPa). Kwon et al [ 103,104 ] utilized ANF as a guest material to construct a reduced graphene oxide (RGO)‐based paper supercapacitor electrode, which exhibited extraordinary tensile strength (100.6 MPa) and superior electrochemical stability. As shown in Figure 18B, the abundant hydrogen bonding and π−π interactions between the RGO and ANF accounted for the impressive strength.…”
Section: Applications Of Anfmentioning
confidence: 99%